PENGARUH KOMPETENSI, INDEPENDENSI, DAN SKEPTISISME PROFESIONAL TERHADAP KUALITAS KINERJA AUDITOR INSPEKTORAT KABUPATEN - FANDI PRASETYA (JIAK : Jurnal Ilmiah Akuntansi dan Keuangan, 2019)
This study aims to determine whether competence, independence, and professional skepticism have a partial effect on the quality of the performance of the district inspector's auditors. The research sample used amounted to 150 determined using the purposive sampling method. The data analysis technique used is by using multiple regression analysis. The results showed that competence, independence, and professional skepticism had a partial effect on the quality of the performance of the district inspector's auditors. So that the higher the competence, independence, and professional skepticism of the auditor, the higher the performance of auditors in the district inspectorate.Keywords: Competence, Independence, Professional Skepticism, Auditor Performance Quality, District Inspectorate